Integrating care between an NHS hospital, a community provider and the role of commissioning: the experience of developing an integrated respiratory service. Issue 12 (21st December 2020) - Banks, Jonathan; Stone, Tracey; Dodd, James
Abstract : Objectives: An integrated respiratory service was commissioned in 2016 in a UK region to support patients with chronic obstructive pulmonary disease. The service brought together the respiratory department of a National Health Service hospital and a not-for-profit community provider. This paper evaluates: (1) the perceived efficacy of integrated working between the organisations from the perspective of staff and (2) the relationship between commissioning and integration of the services. Design: Semistructured interviews with staff from the three organisations involved in the integrated respiratory service. Staff were purposefully sampled. The interviews were audio recorded, transcribed and analysed thematically. Setting: Secondary care respiratory unit; community provider of respiratory care; and a clinical commissioning group. Participants: Nineteen interview participants: nine from the community provider; eight from the hospital and two from the clinical commissioning group. Results: Staff identified lack of integration between the organisations characterised by: poor communication, lack of trust, absence of shared information technology and ineffective integrative initiatives. The commissioning process created barriers to integration including: contractual limitations which prevented pathway development, absence of agreed clinical governance arrangements and lack of recognition of community work undertaken by hospital staff. Positive working relationships were established over time as staff recognised the skills that each had to offer. Conclusions: The commissioning process underpinned the relationship between the organisations and contributed to distrust and negative perceptions of the 'other'. Commissioning an integrated service should incorporate dialogue with stakeholders as early as possible and before the contract is finalised to develop a bedrock of trust.